Lessons for Germany's Gendiagnostikgesetz from Europe's Protocol on Genetic Testing for Health Purposes - Benjamin P. Harbuck (Washington University Global Studies Law Review, 2011)
The Article focuses on the Genetic Diagnosis Act (GenDG) passed by the German Bundestag which regulates the information obtained from the genetic examinations. The details of the GenDG Act and the Protocol on Genetic Testing for Health Purposes are also provided. It also focuses on the genetic testing kits and the flexibility of the Protocol.
Keywords: Genetic disorders -- Diagnosis; Health; Court of Justice of the European Communities; Germany. Bundestag